2020
DOI: 10.3390/biomedicines8080239
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Validation in the Brain Regions of Young Rats after Pentylenetetrazole-Induced Seizures

Abstract: Reverse transcription followed by quantitative polymerase chain reaction (qRT-PCR) is a powerful and commonly used tool for gene expression analysis. It requires the right choice of stably expressed reference genes for accurate normalization. In this work, we aimed to select the optimal reference genes for qRT-PCR normalization within different brain areas during the first week following pentylenetetrazole-induced seizures in immature (P20–22) Wistar rats. We have tested the expression stability of a panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
4
11
0
Order By: Relevance
“…The stability of reference genes could be affected by the types and regions of the samples. In the pentylenetetrazole model of acute seizures, it was found that reference gene stability rankings varied across brain regions, including different areas of the neocortex and the dorsal vs. ventral hippocampus (Schwarz et al., 2020). To date, GAPDH and β‐actin reference genes have predominantly been used as internal reference controls due to their high and constant expression levels in many different cells and tissues (Eisenberg & Levanon, 2013; Zhu et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of reference genes could be affected by the types and regions of the samples. In the pentylenetetrazole model of acute seizures, it was found that reference gene stability rankings varied across brain regions, including different areas of the neocortex and the dorsal vs. ventral hippocampus (Schwarz et al., 2020). To date, GAPDH and β‐actin reference genes have predominantly been used as internal reference controls due to their high and constant expression levels in many different cells and tissues (Eisenberg & Levanon, 2013; Zhu et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In young rats with pentylenetetrazole-induced seizures, the stability of nine tested reference genes, Actb, Gapdh,B2m,Rpl13a,Sdha,Ppia,Hprt1,Pgk1 and Ywhaz,varied significantly between different brain regions (Schwarz et al, 2020). Therefore, the stability of reference genes varies with different experimental settings, tissue types and even different tissue regions (Chapman & Waldenström, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these tools, researchers were able to select the most suitable reference genes and compile specific panels of reference genes for the normalization of expression data adapted to their respective experimental design. Resulting reference genes cover a wide spectrum of research topics, such as human brain samples from patients with neurodegenerative disease [ 41 ], mouse CNS tissue during development and injury [ 42 ], rat brain regions after induced seizures [ 43 ] and specific tissue regions, such as mouse choroid plexus [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of amplification products was carried out using SYBR Green 1 in the presence of ROX reference dye (Evrogen, Russia) according to the manufacturer's recommendations. Expression levels of genes of interest were normalized to the expression of the Ywhaz housekeeping gene (Schwarz et al, 2020) and calculated using the 2 −dCt equation. The sequences of the primers used are shown in Supplementary Table 1.…”
Section: Quantitative Pcrmentioning
confidence: 99%